Britain in the world economy since 1880 - Alford, Bernard W. E. 1937- (Longman, 1996)
Bernard Alford reviews the changing role, and diminishing influence, of Britain within the international economy across the century that saw both the apogee and loss of Britain's empire, and her transformation from globe-straddling superpower to offshore and indecisive member of the European Community. The study of this changing relationship offers a uniquely revealing angle from which to analyse Britain's broader economic development. Professor Alford takes full advantage of that: and his conclusions do not make for comfortable reading.
Keywords: Geschichte 1900-2000; Geschichte 1800-1900; Geschichte 1880-1992; Economische situatie; Internationale economie; Geschichte; Wirtschaft; Wirtschaft. Geschichte; Economic history; International trade; Weltwirtschaft; Großbritannien; Great Britain -- Economic conditions -- 19th century; Great Britain -- Economic conditions -- 20th century; Great Britain -- Commerce -- History -- 20th century; Great Britain -- Commerce -- History -- 19th century